Single-reviewer abstract screening missed 13 percent of relevant studies: a crowd-based, randomized controlled trial - Gartlehner, Gerald; Affengruber, Lisa; Titscher, Viktoria; Noel-Storr, Anna; Dooley, Gordon; Ballarini, Nicolas; König, Franz (Journal of clinical epidemiology, 2020)
To determine the accuracy of single-reviewer screening in correctly classifying abstracts as relevant or irrelevant for literature reviews. We conducted a crowd-based, parallel-group randomized controlled trial. Using the Cochrane Crowd platform, we randomly assigned eligible participants to 100 abstracts each of a pharmacological or a public health topic. After completing a training exercise, participants screened abstracts online based on predefined inclusion and exclusion criteria. We calculated sensitivities and specificities of single- and dual-reviewer screening using two published systematic reviews as reference standards. Two hundred and eighty participants made 24,942 screening decisions on 2,000 randomly selected abstracts from the reference standard reviews. On average, each abstract was screened 12 times. Overall, single-reviewer abstract screening missed 13% of relevant studies (sensitivity: 86.6%; 95% confidence interval [CI], 80.6%–91.2%). By comparison, dual-reviewer abstract screening missed 3% of relevant studies (sensitivity: 97.5%; 95% CI, 95.1%–98.8%). The corresponding specificities were 79.2% (95% CI, 77.4%–80.9%) and 68.7% (95% CI, 66.4%–71.0%), respectively. Single-reviewer abstract screening does not appear to fulfill the high methodological standards that decisionmakers expect from systematic reviews. It may be a viable option for rapid reviews, which deliberately lower methodological standards to provide decision makers with accelerated evidence synthesis products.